Knee Injuries in the Elite American Football Player: A Descriptive Pictorial Imaging and Mechanism of Injury Review. Issue 2 (26th March 2022) - Hernandez, Ricardo J.; Lamplot, Joseph D.; Hammond, Kyle E.; Joshi, Nirav B.; Wong, Phillip K.; Umpirrez, Monica; Singer, Adam; Gonzalez, Felix M.
Abstract: Musculoskeletal injuries are common in American football, with an incidence ranging from approximately 10 to 35 per 1000 playing hours. Injuries occur more commonly in games than in practice. Although several studies have analyzed specific injury types in football, this review aims to describe the most common knee injuries sustained by American football players and to review the existing literature pertaining to the radiologic findings used in the diagnosis of these injuries.